The Comprehensive Understanding of 10 mA cmgeo−2 as an Evaluation Parameter for Electrochemical Water Splitting. Issue 11 (25th July 2018) - Wei, Chao; Xu, Zhichuan J.
Abstract: Comparing the overpotential required to reach the current density of 10 mA cm geo − 2 (per geometric area of an electrode) (η@ 10 mA cm geo − 2 ) is a popular method of ranking electrocatalysts for water‐splitting reactions, i.e., the hydrogen evolution reaction (HER) and the oxygen evolution reaction (OER). However, such methodology is, in essence, not reasonable for studying the intrinsic chemistry difference of electrocatalysts. To have a rational understanding of η@ 10 mA cm geo − 2, here, its historical origin and its limitations on reflecting the intrinsic electrocatalytic activity are discussed. The η@ 10 mA cm geo − 2 is a valid practical parameter to assess water‐splitting devices, but it cannot determine whether a particular electrocatalyst is intrinsically active or not. Abstract : The comprehensive understanding of the overpotential to reach 10 m A c m g e o − 2 is presented, reviewing the historical origin of 10 mA cm geo − 2 as an evaluation parameter for electrochemical water splitting and its limitations on reflecting the intrinsic activity of water‐splitting electrocatalysts.